Mitochondrial DNA copy number in patients with systemic sclerosis - Anastasia I. Bogatyreva; Elena V. Gerasimova; Tatiana V. Kirichenko; Yuliya V. Markina; Taisiya V. Tolstik; Diana G. Kiseleva; Tatiana V. Popkova; Alexander M. Markin; Alexander M. Markin (Frontiers in Molecular Biosciences, 2023)
Introduction: Systemic scleroderma (SSc) is a chronic autoimmune disease of inflammatory origin. Mitochondrial dysfunction is considered as an important mechanism in the pathogenesis of SSc. Currently mitochondrial DNA (mtDNA) copy number is used as a surrogate marker of mitochondrial dysfunction. Previous studies demonstrate that innate immune cells are important participants in inflammatory and fibrotic processes in SSc. The aim of the study was to evaluate the number of mtDNA copies in CD14+ monocytes and whole blood of patients with SSc in comparison with healthy individuals.Methods: Absolute mtDNA copy number was measured using digital PCR. It was found that the number of mtDNA copies in CD14+ monocytes was significantly higher in patients with SSc compared to control, while the number of mtDNA copies in the whole blood did not have significant differences.Results: The correlation analysis revealed an inverse association of mtDNA copy number with disease duration and the relationship between pro-inflammatory activation of CD14+ monocytes in terms of LPS-stimulated IL-6 secretion and mtDNA copy number. At the same time, basal and LPS-stimulated secretion of IL-6 by cultured CD+ monocytes were significantly higher in SSc group in comparison with control.Discussion: The study results suggest that increase of mtDNA copy number in CD14+ monocytes is a possible mechanism to maintain the reduced function of defective mitochondria in monocytes from patients with SSc associated with the development and progression of SSc.